2014
DOI: 10.1007/s10753-014-9911-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum GP88 (Progranulin) Concentrations in Rheumatoid Arthritis

Abstract: GP88 (Progranulin; PGRN) is a secreted glycosylated protein with important functions in several processes, including immune response and cancer growth. Recent reports have shown that PGRN is a therapeutic target for rheumatoid arthritis (RA) because of its capability to bind with tumor necrosis factor receptor (TNFR). However, the serum PGRN level in RA patients has not been investigated. We used enzyme-linked immunosorbent assay (ELISA) to quantify the serum levels of PGRN in 417 healthy subjects, 56 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 30 publications
7
53
1
2
Order By: Relevance
“…PGRN is expressed in a broad range of tissues and cell types including epithelial cells, neurons, macrophages, skeletal muscle, chondrocytes, adipose tissue, hematopoietic cells, and immune cells, including T cells and DCs [22,23]. The levels of PGRN were found to be elevated in cancers, rheumatoid arthritis, activated microglia in many neurodegenerative diseases, and neutrophils that promoted antibody diversity in B cells [24][25][26][27][28]. It was previously demonstrated that the expression of PGRN in intact skin is low, but in injured skin, it raises significantly [29].…”
Section: Discussionmentioning
confidence: 99%
“…PGRN is expressed in a broad range of tissues and cell types including epithelial cells, neurons, macrophages, skeletal muscle, chondrocytes, adipose tissue, hematopoietic cells, and immune cells, including T cells and DCs [22,23]. The levels of PGRN were found to be elevated in cancers, rheumatoid arthritis, activated microglia in many neurodegenerative diseases, and neutrophils that promoted antibody diversity in B cells [24][25][26][27][28]. It was previously demonstrated that the expression of PGRN in intact skin is low, but in injured skin, it raises significantly [29].…”
Section: Discussionmentioning
confidence: 99%
“…PGRN has been reported to show a therapeutic effect in vivo through its interaction with TNFRs in multiple murine models of inflammatory arthritis . Moreover, the PGRN/TNFR interaction has been confirmed and extended in multiple disease models …”
Section: Pgrn Modulates Tnf/tnfr Signalingmentioning
confidence: 87%
“…RA is a chronic autoimmune disease characterized by typical synovial and articular cartilage damage, finally leading to joint dysfunction with varied clinical presentations . PGRN level is elevated in both serum and synovial fluid in patients with RA, and this increased level of PGRN correlates with disease activity . Given that TNF‐α acts as a chief mediator of proinflammatory cascade responses in RA and that PGRN disturbs TNF‐α/TNFR signaling, Tang et al .…”
Section: Pgrn In Inflammatory Arthritismentioning
confidence: 99%
See 2 more Smart Citations